If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -42(0) + 7 = 0 Multiply -42 * 0 7y + 0 + 7 = 0 Anything times zero is zero. 7y + 0 + 7 = 0 Reorder the terms: 0 + 7 + 7y = 0 Combine like terms: 0 + 7 = 7 7 + 7y = 0 Solving 7 + 7y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 7y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 7y = 0 + -7 7y = 0 + -7 Combine like terms: 0 + -7 = -7 7y = -7 Divide each side by '7'. y = -1 Simplifying y = -1
| -3=6n-5n | | -69+11x=x+61 | | w-2-3h=52 | | 8x-14=(x^2)+1 | | 4x+-4x=-1x+-1 | | 61=4x-13 | | -2(x-4)(x+3)=0 | | log^3(x)=log^9(3*x+18) | | 1b=-42 | | 12x+8y=138 | | (X+11)(x+3)=240 | | x*(2x+7)=460 | | 1/3*2.25 | | (3z-5)(3z+15)=0 | | W=(.0026*65*1000*^(3)/1.5 | | 4x+-4=-4x+6 | | 3m+9=4(2m+6) | | -10v=6 | | 22.1+.21x=24.94+.16x | | 12y+9x=294 | | -(x-1)(x-5)(x-10)=0 | | 6sinx+5cosx=2 | | 0.8d+3.74=d+1.5 | | 6+5(-6x+3)=-4 | | 4/n=11 | | -16-10x=-7x+38 | | 90=3.5x | | H/8=3 | | 100=10Q(x)+5Q(Y) | | -5n-24+n^2=0 | | 20/3=m30 | | 2x+18=55 |